Comparison Between Physical Exercise and Alendronate Against Bone Calcium Levels and Body Weight In Wistar Rats Model Glucocorticoid-Induce Osteoporosis - Hanna Cakrawati; Minarma Siagian; Neng Tine Kartinah (Saintika Medika, 2022)
Glucocorticoid-induce osteoporosis (GIO) is a bone condition with osteoporosis due to taking long-term glucocorticoid drugs which is the most common cause of increasing the number of fracture cases which is a health problem. GIO is one of the most common forms of osteoporosis in men. Sodium alendronate is a biphosponate drug that is approved for prevention and management of GIO but has serious side effects on long-term use. Doing physical exercise "weight-bearing exercise" such as running is known to increase BMD (Bone Mineral Density) and can reduce osteoponia and the risk of osteoporosis. This study was a study with experimental studies, using male Wistar rats aged 8 weeks divided randomly into 4 groups, namely 1) positive control group (given oral prednisolone 0.54 mg/200g/day), 2) negative control group (not given oral prednisolone), 3) physical exercise group and 4) oral administration group of sodium alendronate (0.09 mg / 200g / day). Bone density will be measured by measuring the calcium level of the tibia bone using the AAS (Atomic Absorptions Spectrophotometer) method and the body weight of mice using scales. The results showed that physical exercise and sodium alendronate significantly affected p = 0.029 with (p <0.05) increasing calcium levels in rats induced by glucocorticoids and obtained p = 0.064 with (p <0.05) in this study there was no difference significant body weight difference between research groups